LA UNIFICACIÓN DEL SISTEMA DE INSPECCIÓN LABORAL Y LA SUPERVISION Y FISCALIZACION DEL CUMPLIMIENTO DE LAS NORMAS SOCIOLABORALES - Reyes Avalos, Gisela Lizeth (2018)
The Peruvian Labor Inspection System is a current and interesting topic, which is becoming more important every day, and more so with the current publication of Law N ° 30814 "Law on Strengthening Labor Inspection"; in which, the Regional Governments grant the powers and control functions to the Sunafil, for a period of 8 years, and may be extended after evaluation of the results obtained by the Sunafil; being this, the only administrative authority in charge of the Labor Inspection System. In that sense; the thesis presents, focuses on analyzing what are the advantages of the unification of the Labor Inspection System in Supervision and Supervision of compliance with social and labor standards in Peru; for this, the present Final Report of Thesis denominated: "The Unification of the System of Labor Inspection and the Supervision and Inspection of the socio-labor Norms" is divided into two parts: Methodological Framework and Theoretical Framework. In the theoretical framework of the present investigation, a detailed review was made of the Labor Inspection System, the International Labor Organization (ILO) agreements concerning the Labor Inspection System, the Peruvian Labor Inspection System, the unification of the Labor Inspection and the supervision and supervision of compliance with social and labor standards. Finally, an analysis was made in light of the administrative jurisprudence, of two cases, one of the Sunafil and another of the Regional Management of Labor and Promotion of Employment (GRTYPE) of Freedom, on the Supervision and Supervision of Compliance with social and labor standards.